Evaluating Bahasa Inggris Maritim dan Perikanan Paket Keahlian Teknika Kapal Penangkapan Ikan Kelas X - Mella, Stellar Nube (JET ADI BUANA, 2019)
This study would like to find out the extent to which the ESP textbooks Bahasa Inggris Maritim dan Perikanan Paket Keahlian: Teknika Kapal Penangkapan Ikan Kelas X Semester I (BIMP I) and Bahasa Inggris Maritim dan Perikanan Paket Keahlian: Teknika Kapal Penangkapan Ikan Kelas X Semester II (BIMP II) met the criterions of ESP textbooks evaluation proposed by Cunningsworth (1995). Content analysis was used to analyze the textbooks. It was found that one of the textbooks’ objectives was to enable students to use English as a communication tool. Both ESP textbooks presented vocabulary and discourse structures, covered relevant skills, encouraged learning activities relevant to student’s real life, and acknowledged student’s subject specific knowledge. The presentation of language items and language skills, however, were not fully in balance, and both ESP textbooks did cover speaking activities which replicated genuine English communication.